Respuestas

  • Usuario de Brainly
2013-06-22T21:09:58+02:00
A) -3x+3y=6
     -5x-y=-8
-3x + 3y = 6 → 3y = 6 + 3x → y = 6/3 + 3/3x → y = 2 + x
-5x - y = - 8 → - y = - 8 + 5x → y = 8 - 5x
2 + x = 8 - 5x
x + 5x = 8 - 2
6x = 6
x =  6/6
x = 1
y = 2 + x → y = 2 + 1 → y = 3
Conjunto de solución (1 ; 3)
 
 
B) 2x-3y=1
   3x-4y=-1                          
 2x - 3y = 1 → - 3y = 1 - 2x → y = -1/3 + 2x/3
3x - 4y = - 1 → -4y = -1 - 3x → y = 1/4 + 3x/4
-1/3 + 2x/3 = 1/4 +3x/4
2x/3 - 3x/4 = 1/4 + 1/3
-1x/12 = 7/12
x = 7/12 : - 1/12
x = - 7
y = -1/3 + 2(-7)/3
y = - 1/3 - 14/3
y = - 15/3
y = - 5
Conjunto de solución (- 7 , - 5)

C) -3x-4y=1
    4x-5y=-1
- 3x - 4y = 1 →-4y = 1 + 3x → y = -1/4 - 3x/4
4x - 5y = -1 → -5y = -1 -4x → y = 1/5 + 4x/5
-1/4 - 3x/4 = 1/5 + 4x/5
-3x/4 - 4x/5 = 1/5 + 1/4
-31x/20 = 9/20
x = 9/20 : - 31/20
x = - 9/31
y = -1/4 - 3x/4
y = -1/4 - 3(-9/31)/4
y = -1/4 + 27/124
y = - 1/31
Conjunto de solución (-9/31, - 1/31)
 
D) 3x+y= - 2
   -5x+2y=3

3x + y = - 2 →y = - 2 -3x
-5x + 2y = 3 → 2y = 3 + 5x → y = 3/2 + 5x/2
-2 - 3x = 3/2 + 5x/2
- 2 -3/2 = 5x/2 + 3x
- 7/2 = 11x/2
- 7/2 : 11/2 = x
-7/11 = x
y = - 2 - 3x
y = - 2 - 3(-7/11)
y = - 2 + 21/11
y = - 1/11
Conjunto de solución ( - 7/11, -1/11 )

espero que te sirva, salu2!!!!